STALK WATER POTENTIAL IN RELATION TO CHARCOAL ROT OF SORGHUM - C. D. MAYEE, S. M. PEDGAONKAR AND (Indian Phytopathology, 2002)
An investigation on water potential of sorghum stalk revealed that absolute water content (AWC) and water saturation deficit (WSD) varied substantially amongst the genotypes differing in resistance to charcoal rot pathogen. Cultivars CS-3S41 and PVK-3 which were low susceptible to charcoal rot exhibited high AWC and low depletion rate than the susceptible cultivars, CSH-1 and RÂ·16. After inoculation, AWC normally decreased irrespective of cultivar. However, AWC drastically declined in susceptible cultivars. WSD, which is useful indicator of the water status of a plant, increased substantially in inoculated plants of CSH-1 and R-16 and effects were more pronouneed after flowering when the disease expresses. The rate of RSM was high in the susceptible cultivars than the resistance ones.